Design of Expert System for Decision Making in Materials Purchasing - Torres Navarro, Carlos Alonso; Córdova Neira, Javier Andrés (Cuadernos de Administración, 2014)
The aim of this research was to verify the feasibility of integration between inventory theories and expert systems theories by designing an information system based on knowledge to support the decision making process in the logistics and supply area of a leading forestry company in Latin America. The methodology used consisted in a review of scientific publications, accessed online, on inventory models, multiple criteria ABC classification criteria, and identification of the components of expert systems based on knowledge. The results permit having an expert system design supported by Excel spreadsheets, macro programming in Visual Basic, and interaction with an information system on entrepreneurial resource planning. The main conclusions indicate that it is feasible to integrate between the theory of inventories, the use of a multiple criteria ABC classification with the theory of expert systems based on tacit and explicit type knowledge and, additionally, it is possible to achieve a reduction of 40% of the working capital retained in inventories